Relation between solar light intensity and vertical distribution of krill swarms - Katsuhiko Kubota (National Institute of Polar Research, 1981)
In order to study the relation between solar light intensity and vertical distribution of krill swarms, the author examined the records of light intensity measured by a photometer and the images of krill swarms taken through a fish finder on board the KAIYO MARU in the area south of 61°S between 100°E and 120°E during her first antarctic cruise in the 1979-80 season. The krill swarms occurred above the 100m depth. They concentrated in the surface layer above the 20m depth at night between 1820 and 0420 (local time) and in the 20 to 40m depth layer at daytime. The light intensities at sunrise, noon, sunset and midnight were 90 to 520lx, 30000 to 124000lx, 80 to 420lx and 0 to 30lx, respectively. The diurnal migration of krill swarms in relation to the solar light intensity was confirmed.